Examining Multiteam Systems Across Context and Type: A Historiometric Analysis of Failed MTS Performance - Campbell, Lauren N. P.; Torres, Elisa M.; Zaccaro, Stephen J.; Zhou, Steven; Hedrick, Katelyn N.; Wallace, David M.; Luning, Celeste Raver; Zakzewski, Joanna E. (Frontiers in Psychology, 2022)
Multiteam systems (MTSs) are complex organizational forms comprising interdependent teams that work towards their own proximal goals within and across teams to also accomplish a shared superordinate goal. MTSs operate within high-stakes, dangerous contexts with high consequences for suboptimal performance. We answer calls for nuanced exploration and cross-context comparison of MTSs “in the wild” by leveraging the MTS action sub-phase behavioral taxonomy to determine where and how MTS failures occur. To our knowledge, this is the first study to also examine how key MTS attributes (boundary status, goal type) influence MTS processes and performance. We conducted historiometric analysis on 40 cases of failed MTS performance across various contexts (e.g., emergency response, commercial transportation, military, business) to uncover patterns of within- and between-team behaviors of failing MTSs, resulting in four themes. First, component teams of failing MTSs over-engaged in within-team alignment behaviors (vs. between-team behaviors) by enacting acting, monitoring, and recalibrating behaviors more often within than between teams. Second, failing MTSs over-focused on acting behaviors (vs. monitoring or recalibrating) and tended to not fully enact the action sub-phase cycle. Third and fourth, boundary status and goal type exacerbated these behavioral patterns, as external and physical MTSs were less likely to enact sufficient between-team behaviors or fully enact the action sub-phase cycle compared to internal and intellectual MTSs. We propose entrainment as a mechanism for facilitating MTS performance wherein specific, cyclical behavioral patterns enacted by teams align to facilitate goal achievement via three multilevel behavioral cycles (i.e., acting-focused, alignment-focused, and adjustment-focused). We argue that the degree to which these cycles are aligned both between teams and with the overarching MTS goal determines whether and how an MTS fails. Our findings add nuance beyond single-context MTS studies by showing that the identified behavioral patterns hold both across contexts and almost all types of MTS action-phase behaviors. We show that these patterns vary by MTS boundary status and goal type. Our findings inform MTS training best practices, which should be structured to integrate all component teams and tailored to both MTS attributes (i.e., boundary status, goal type) and situation type (e.g., contingency planning).